Chryso-lactams:Gold(I) derivatives of ampicillin with specific activity against Gram-positive pathogens. Issue 9 (1st May 2020) - Michaut, Mathieu; Steffen, Alexandre; Contreras, Jean-Marie; Morice, Christophe; Paulen, Aurélie; Schalk, Isabelle J.; Plésiat, Patrick; Mislin, Gaëtan L.A.
Graphical abstract: